The Integrated Role of Individual Characteristics, Self-Efficacy, and Competence in Improving Employee Performance - Ni Kadek Ayu Novita Sari; Ni Made Dwi Puspitawati; Tiara Carina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Employee performance refers to the work results and work behavior achieved in completing assigned tasks and responsibilities within a specific period. This study was conducted to examine the influence of individual characteristics, self-efficacy, and competence on employee performance at the Infinity Training Centre Badung. The study population consisted of all 34 employees at the Infinity Training Centre Badung, and a saturated sample was used. To achieve the desired objectives, the study employed multiple linear regression. The results indicated that individual characteristics have a positive and significant effect on employee performance at the Infinity Training Centre Badung, self-efficacy has a positive and significant effect on employee performance at the Infinity Training Centre Badung, and competence has a positive and significant effect on employee performance at the Infinity Training Centre Badung.